Problems of Applying the Teaching of Speech Skills in Arabic in Light of the Covid-19 Pandemic: مشكلات تطبيق تعليم مهارة الكلام باللغة العربية فى ظل جائحة كوفيد -19 (دراسة حالة فى قسم الاقتصاد الإسلامي جامعة كديري الإسلامية الحكومية) - Mokhammad Miftakhul Huda (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2021)
The background of this research is the problem of applying maharah kalam learning in Arabic in the scope of higher education when the covid 19 pandemic outbreak. The Indonesian government has declared a state of emergency related to the Corona virus, and the Minister of Education and Culture has launched home learning since March . Online learning is being carried out to stop the spread of the outbreak. In general, students still have difficulty recognizing letters and learning long-distance speaking (muhadatsah) skills. This type of research is qualitative research, which is scientific activities to analyze social phenomena that exist among us to find out the truth that is beneficial to society. The objectives of this study are: 1) Problems in the application of Arabic speaking skills in Syari'ah Economics Study Program IAIN Kediri. 2) Solutions for the application of Arabic speaking skills in the Syari'ah Economics Study Program of IAIN Kediri. The results of this study are; 1) the government must expand and improve good internet access, 2) educators must be able to provide educational material according to student needs, motivation and encouragement must be given to students during distance education, 3) parents must pay attention to their children's learning, 4) Students able to take advantage of existing opportunities.